Integrative analysis for the discovery of lung cancer serological markers and validation by MRM-MS - Shin, Jihye; Song, Sang-Yun; Ahn, Hee-Sung; An, Byung Chull; Choi, Yoo-Duk; Yang, Eun Gyeong; Na, Kook-Joo; Lee, Seung-Taek; Park, Jae-Il; Kim, Seon-Young; Lee, Cheolju; Lee, Seung-won (PUBLIC LIBRARY SCIENCE, 2017)
Non-small-cell lung cancer (NSCLC) constitutes approximately 80% of all diagnosed lung cancers, and diagnostic markers detectable in the plasma/serum of NSCLC patients are greatly needed. In this study, we established a pipeline for the discovery of markers using 9 transcriptome datasets from publicly available databases and profiling of six lung cancer cell secretomes. Thirty-one out of 312 proteins that overlapped between two-fold differentially expressed genes and identified cell secretome proteins were detected in the pooled plasma of lung cancer patients. To quantify the candidates in the serum of NSCLC patients, multiple- reaction-monitoring mass spectrometry (MRM-MS) was performed for five candidate biomarkers. Finally, two potential biomarkers (BCHE and GPx3; AUC = 0.713 and 0.673, respectively) and one two-marker panel generated by logistic regression (BCHE/GPx3; AUC = 0.773) were identified. A validation test was performed by ELISA to evaluate the reproducibility of GPx3 and BCHE expression in an independent set of samples (BCHE and GPx3; AUC = 0.630 and 0.759, respectively, BCHE/GPx3 panel; AUC = 0.788). Collectively, these results demonstrate the feasibility of using our pipeline for marker discovery and our MRM-MS platform for verifying potential biomarkers of human diseases.
Keywords: GLUTATHIONE-PEROXIDASE GPX3; CHOLINESTERASE ACTIVITY; BIOMARKER CANDIDATES; MASS-SPECTROMETRY; PROTEOMICS; PREDICTION; ADENOCARCINOMA; QUANTIFICATION; QUANTITATION; VERIFICATION